RETARD DIAGNOSTIQUE ET IMPLICATION PRONOSTIQUE EN MILIEU AFRICAIN. CAS DES URGENCES EN CHIRURGIE DIGESTIVE À L’HÔPITAL NATIONAL DE ZINDER, NIGER - Harissou, Adamou; Ibrahim, Amadou M M; Oumarou, Habou; Mansour, Adamou; Amadou, Magagi; Ousseni, Elh Adakal; Niandou, Mahaman; Rachid, Sani (European Scientific Journal, ESJ, 2015)
Purpose: this study aimed to analyze the epidemiological aspects and evaluate the impact of late diagnosis on prognosis of gastrointestinal surgical emergencies at the National Hospital of Zinder (Niger). Patients and method: this is a prospective study from 1 January to 31 December 2013. All patients underwent surgery for digestive emergency were included. Results: We collected 302 patients. Emergencies digestive surgery accounted for 22% of 1358 cases of surgical emergencies recorded over the period of the study period. The sex ratio is 3/1 in favor of men. The average age of patients was 23 years. Digestive surgical emergencies affect more children (45%) and young adults (43%). The majority (70%) of our patients did not attend school and 49% were from rural areas. The diagnosis delay rule, 171 patients (57%) arrived to emergency department more than 48 hours after onset of symptoms. Abdominal pain with or without other signs was the main reason for consultation (92% of patients). 182 patients had a poor general status. The etiologies were dominated by peritonitis (52%) followed by intestinal obstruction (28%), and abdominal trauma with 10% of cases. The parietal suppuration isolated or associated with other morbidities was the main postoperative (28%). The average length of hospital stay was 9 days. 36 patients (12%) had died. Almost half of the deaths (47%) occurred within the first 48 hours of admission. The delay of admission and the surgical management was statistically significant effect on the prognosis (P<0.006, p< 0.0001). Conclusion: The prognosis of gastrointestinal surgical emergencies is highly correlated with the speed of diagnosis leading to appropriate treatment as soon as possible. This promptness is the only guarantee of a decline in the high morbidity and mortality which is often linked to dysfunction of our hospitals and/or accessibility problems faced by patients.